ЕВАЛУАЦИЈА НА ИНТЕРСТИЦИЕЛНИ БЕЛОДРОБНИ ЗАБОЛУВАЊА СО РАДИОЛОШКА МЕТОДА НА КОМПЈУТЕРСКА ТОМОГРАФИЈА СО ВИСОКА РЕЗОЛУЦИЈА И НИВНА КОРЕЛАЦИЈА СО КЛИНИЧКА СИМПТОМАТОЛОГИЈА - Dimitrijevikj, Kristina (My University, 2024)
Introduction: Interstitial lung diseases are a heterogeneous group of characteristic lung diseases, classified on the basis of radiological, clinical or pathological factors, which cause fibrotic changes of lung tissue in different stages of the disease. HRCT has revolutionized the diagnosis of diffuse lung diseases, especially in the recognition of HRCT characteristic changes of the interstitium with the visibility of lesions at the level of the secondary lobule, which was previously impossible with the older generations of CT. The aim of the study: To evaluate the value of HRCT in the diagnosis of certain interstitial lung diseases. To correlate the radiological stage with the clinical finding, to determine the stage in the progression of interstitial lung diseases, to establish a radiological algorithm with a gradual approach in the diagnosis of IBB, as well as to timely diagnose the early stage of interstitial fibrosis. Material and Methods: A total of 130 patients aged between 18 – 85 years old with clinical indication of interstitial lung disease who were hospitalized or came as an outpatient to the Clinic for Pulmonology and Allergology - Skopje participated in this study. Data were collected with a 20-question patient questionnaire. The method used was HRCT, which was performed at the University of Pulmonology and Allergology - Skopje with a PHILIPS INCISIVE device with 128 slices in the supine position with a standard protocol. The patients were selected in three groups where the distribution of HRCT between UIP and NSIP pneumonia and their correlation with clinical symptomatology was first evaluated, then an analysis was made of the distribution of HRCT findings in sarcoidosis and their correlation with symptoms and the third group was composed of rare interstitial lung diseases found in our country and they were descriptively treated. Results: Radiological changes were entered into a form for distribution of HRCT findings, and then the same were statistically processed. The type of interstitial lung changes and their distribution were correlated with the clinical symptomatology. A total of 70 patients participated in the first group of the research, of which 30 patients with non-specific interstitial pneumonia, 40 patients with common interstitial pneumonia. The gender structure of patients from both groups was homogeneous, that is, statistically insignificantly different (p=0.48). Female patients were more often represented in both groups (63.33% in NSIP, 55% in UIP). The two studied groups differed significantly in terms of age (p=0.039). Patients with NSIP were significantly younger than patients with UIP (61.1 ± 14.1 vs 66.8 ± 8.5 years, respectively. Difficulty breathing was the predominant symptom in patients from both groups, that is, 96.67% of patients with NSIP and 91.89% of patients with UIP had dyspnea. HRCT reticular opacities in the upper and middle zones were more often seen in UIP patients compared to NSIP patients, with a statistically insignificant difference for peripheral and subpleural localization (97.5% vs 90%, p=0.18), and a statistically significant difference for peribronchovascular localization (12.5% vs 0%, p=0.044). In the lower lung zones, HRCT findings regarding the frequency of reticular opacities differed significantly between NSIP and UIP groups for peripheral and subpleural localization (p=0.017), not significantly for peribronchovascular localization (p=0.38). Reticular opacities in the peripheral and subpleural regions were seen in 86.67% of NSIP patients and all UIP patients, while such a finding in the peribronchovascular regions was seen in only 1 patient of the UIP group. Patients with NSIP significantly more often than patients with UIP had a HTCT finding of high attenuation in the peripheral and subpleural regions in the upper and middle zones (23.3% vs 5%, p=0.023), and non-significantly more often in the peribronchovascular regions of the upper and middle zones ( 36.67% vs 17.5%, p=0.07). HRCT findings of low attenuation in the upper and middle peripheral and subpleural zones were significantly more frequent in patients with UIP compared to patients with NSIP (77.5% vs 46.67%, p=0.0077). In the lower lung zones, HRCT findings regarding the frequency of reticular shadows differed significantly between NSIP and UIP groups for peripheral and subpleural localization (p=0.017). HRCT findings of high attenuation in the lower peripheral and subpleural zones were significantly more frequent in patients with NSIP, that is, this finding was not registered in the group with UIP (30% vs 0%, p=0.0077). High attenuation in the peribronchovascular regions of the lower zones was detected in 53.33% of patients with NSIP, 62.5% of patients with UIP, without a statistically significant difference between the two groups. The second group systematized for statistical analysis included 50 patients diagnosed with sarcoidosis. The gender structure of the patients is predominantly made up of female patients - 46(92%) vs 4(8%). The patients were aged from 30 to 73 years, with an average age of 52.6 ± 12.5 years, and with a place of residence mostly in an urban environment – 42(84%) vs 8(16%). Regarding the smoking status, 8(16%) patients declared themselves as current smokers, 28(56%) as ex-smokers, with an average smoking experience of 14.9 ± 4.8 years. The time when they stopped smoking ranges between 4 and 27 years, on average, ex-smokers stopped smoking 11.9 ± 7.1 years ago. The localization of micronodular changes larger than 3 mm in the upper and middle zones had an identical distribution peripherally subpleural and peribronchovascular – 10 (20%). Identical peripheral subpleural and peribronchovascular localization of micronodular changes larger than 3mm was also detected in the lower zones – 2(4%). Bilateral lymphadenopathy by HRCT was diagnosed in 34(68%) patients, right paratracheal lymphadenopathy in 40(80%) patients, in other nodal stations in 36(72%) patients, and in 10(20%) patients conglomerated lymph nodes were seen. Calcified lymph nodes were presented in 16(32%) patients: focal large calcifications in 12(24%) patients, punctiform in 2(4%) patients, scaly also in 2(4%) patients. In the third group, 10 patients with rare interstitial lung diseases in our country were descriptively analyzed without adequate statistical analysis due to the small number of patients. Conclusion: This study cast a new view between theory, clinical practice and radiological diagnosis in the treatment of pulmonary interstitial diseases. Analysis of the type of patterns of interstitial lung changes with their distribution and correlation with clinical symptomatology, narrows the differential diagnosis in these diseases and enables reliable detection of early changes, and thus early and timely treatment. The diagnosis, management and therapy of interstitial lung diseases (ILD) show a need for multicenter projects and studies where collaboration between pulmonologists, radiologists, thoracic surgeons and pathologists is required. HRCT analysis of IBD patients accumulates a large amount of images and data that initiates the consideration of artificial intelligence assistance. Artificial intelligence and knowledge supported by machines that perform quantitative and automatic analysis in ILD will increase in importance in the future, but further improvements and validations are needed. However, radiologists still have a central role in the clinical management and research of interstitial lung diseases. Key words: lungs, interstitial lung disease, high-resolution computed tomography, UIP, NSIP, sarcoidosis.